Tantangan penegakan HAM dalam ruang siber: Efektivitas UU PDP terhadap ancaman eksploitasi data pribadi masyarakat - Ikhsan, Maulana (Maliki Interdisciplinary Journal, 2026)
The rapid advancement of digital technology has brought significant changes to society, yet it has also opened new vulnerabilities to personal data exploitation in cyberspace. This study aims to examine the challenges of enforcing Human Rights (HAM) in the digital context, particularly regarding the effectiveness of Law Number 27 of 2022 on Personal Data Protection (UU PDP) in safeguarding the fundamental rights of Indonesian citizens. A descriptive qualitative method with a literature study approach was employed, analyzing various legal sources, academic journals, and related regulations. The findings reveal that while UU PDP has provided a stronger legal framework compared to previous regulations, several weaknesses remain in terms of institutional capacity, sanction enforcement, and public awareness. The foundational values of Pancasila as the basis of national life should serve as the primary foundation in building a just and sovereign data protection system. Strengthening supervisory institutions, enhancing digital literacy, and harmonizing regulations are necessary to ensure effective and comprehensive protection of human rights in cyberspace.